CONSORT extension for reporting N-of-1 trials (CENT) 2015: Explanation and elaboration. (14th May 2015) - Shamseer, Larissa; Sampson, Margaret; Bukutu, Cecilia; Schmid, Christopher H; Nikles, Jane; Tate, Robyn; Johnston, Bradley C; Zucker, Deborah; Shadish, William R; Kravitz, Richard; Guyatt, Gordon; Altman, Douglas G; et al.
Abstract : N-of-1 trials are a useful tool for clinicians who want to determine the effectiveness of a treatment in a particular individual. The reporting of N-of-1 trials has been variable and incomplete, hindering their usefulness in clinical decision making and by future researchers. This document presents the CONSORT (Consolidated Standards of Reporting Trials) extension for N-of-1 trials (CENT 2015). CENT 2015 extends the CONSORT 2010 guidance to facilitate the preparation and appraisal of reports of an individual N-of-1 trial or a series of prospectively planned, multiple, crossover N-of-1 trials. CENT 2015 elaborates on 14 items of the CONSORT 2010 checklist, totalling 25 checklist items (44 sub-items), and recommends diagrams to help authors document the progress of one participant through a trial or more than one participant through a trial or series of trials, as applicable. Examples of good reporting and evidence based rationale for CENT 2015 checklist items are provided.